CO2 Cycloaddition to Epoxides by using M-DABCO Metal–Organic Frameworks and the Influence of the Synthetic Method on Catalytic Reactivity; ChemistryOpen; Vol. 6, iss. 5 - Mousavi B. Bibimaryam; Chaemchuen S. Somboon; Moosavi B. Behrooz; Zhou K. Kui; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Verpoort F. V. K. Frensis Valter Kornelius (2017, 2017)
Title screen